Tuning the donating strength of dye sensitizers using molecular electrostatic potential analysis. (22nd January 2021) - Divya, Velayudhan V.; Suresh, Cherumuttathu H.
Abstract : The significance of electron releasing groups at the donors of D–π–A systems for improving the donating strength and power conversion efficiency of photosensitizers. Abstract : Donor–π–acceptor (D–π–A) systems typically used in dye-sensitized solar cells (DSSC) have been studied for assessing the donating strength of six donors (D1–D6) under the influence of substituents such as CH3, C5 H11, isopropyl, t -butyl, OH, OCH3, OC2 H5, NH2, N(CH3 )2, PhCH3, and PhNH2 along with π-spacer butadiene and acceptor moiety cyanoacrylic acid. The substituent effect enhances electron donation from D to A through the π-spacer. The enhancement in electron density at A has been quantified in terms of the difference in the molecular electrostatic potential (MESP) minimum at the cyano nitrogen (Δ V mA ) between π–A and D–π–A. For unsubstituted D–π–A systems, Δ V mA is in the range −0.1 to −5.7 kcal mol −1, whereas the substitution enhances the negative character of Δ V mA in the range −0.8 to −8.0 kcal mol −1 . In alkyls and Ph–CH3 substituted D–π–A systems, Δ V mA lies in the range −0.8 to −6.7 kcal mol −1, whereas the N(CH3 )2 substituted systems exhibit more negative Δ V mA (more enhanced donating strength) in the range −5.1 to −8.0 kcal mol −1 . The more negative value of Δ V mA implies the greater electron-donating ability of the D−π−A system. Optical and photovoltaic parameters (Δ G reg, Δ G inject, e V OC ) are analyzed at the TD-CAM-B3LYP/SMD/cc-pVDZ//B3LYP/cc-pVDZ level of DFT. An excellent linear correlation is observed in all six sets between Δ V mA and the absorption maximum ( λ max ) showing that λ max increases with enhanced donating strength. The higher absorption maximum obtained by N(CH3 )2 substituted D–π–A systems lies in the range 430 nm to 490 nm, explaining the outstanding donating ability of N(CH3 )2 compared to other substituents. The reduced highest occupied molecular orbital (HOMO) – lowest unoccupied molecular orbital (LUMO) gap (from 3.14 to 2.17 eV) with enhanced donating strength confirms the influence of substituent effects in broadening the absorption maximum. Furthermore, in photovoltaic parameters, a strong influence of the substituent effect is observed. The N(CH3 )2 substituted D1–π–A (D1–N(CH3 )2 ) exhibits the highest e V OC (1.38 eV). The strong linear correlation observed for the ground state property Δ V mA and open-circuit voltage e V OC provides guidelines for developing an effective strategy for designing dye sensitizers for desirable photovoltaic applications.